2013
DOI: 10.18052/www.scipress.com/ilcpa.12.120
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Ultrasonic Velocities in Binary Liquid Mixture Containing Aniline and Anisole at Different Temperatures – A Comparative Study

Abstract: Ultrasonic velocity is measured experimentally at 3MHz frequency in the binary liquid mixture containing aniline and anisole at different temperatures over the entire composition range and theoretical values of ultrasonic velocity have been evaluated by using Nomoto's relation, Impedance relation, Van Dael ideal mixture relation. These theoretical values are compared with the experimental values. A good agreement has been found between experimental and theoretical ultrasonic velocities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The values of adiabatic compressibility () can be calculated by the following relation: where u is ultrasonic velocity and p is density. The experimentally measured values of pure components are compared with the literature [9][10][11][12][14][15][16][17] values and are given in (Table 1). …”
Section: Theorymentioning
confidence: 99%
“…The values of adiabatic compressibility () can be calculated by the following relation: where u is ultrasonic velocity and p is density. The experimentally measured values of pure components are compared with the literature [9][10][11][12][14][15][16][17] values and are given in (Table 1). …”
Section: Theorymentioning
confidence: 99%
“…where u is ultrasonic velocity and p is density. The experimentally measured values of pure components are compared with the literature [9][10][11][12][14][15][16][17] values and are given in (Table 1). 2 it is observed that the ultrasonic velocity increases with increase in mole fraction of 1-butanol.…”
Section: Molar Volume (mentioning
confidence: 99%
“…The intermolecular free length decreases with decrease of temperature and hence the close packing of molecules which in effect decreases the sound velocity [5,6]. The compressibility decreases with increase of velocity that gives insight into the structure making and structure breaking of components in binary mixtures [7,[18][19][20]. In this work we report the experimental values of the density, viscosity and ultrasonic velocity of the above binary mixtures at the temperatures 298.15 and 308.15 K. These data have been used to calculate various acoustical parameters like adiabatic compressibility (β), free volume (V f ) and free length (L f ).…”
Section: Introductionmentioning
confidence: 99%